A Survey of Program Directors: Trends, Challenges, and Mentoring in Prosthodontics. Part 1 - Robert F. Wright, DDS, FACP,1 Ryan A. Dunlop, DMD,2 Frances M. Kim, DDS, MPH, DPH,3 (Journal of Prosthodontics, 2008)
This study consisted of two parts. Part 1, a survey of program directors, was conducted to examine current trends in advanced education in prosthodontics in the United States